Analisis Kedisiplinan Mahasiswa Bimbingan Konseling Pendidikan Islam Semester 6 - Sri Puspita Della Aryadi; Arlina Arlina; Muhammad Nur Huda; Dessy Tri Afifah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to determine the discipline of students in the Islamic Education Guidance and Counseling Study Program Semester 6. This type of research is qualitative descriptive research with a phenomenological research method. The research objects were students of the 6th Semester Islamic Education Guidance and Counseling Study Program which were determined using purposive sampling. Data collection instruments use interview guidelines and are supported by observation and documentation activities. The research results show that indiscipline has a negative impact on the perpetrators, such as not understanding the material presented at the beginning, not being allowed to enter class, and resulting in poor final assessment results by the lecturer.